2014
DOI: 10.3109/14767058.2014.979783
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopmental outcomes of premature infants with severe intraventricular hemorrhage

Abstract: Our results demonstrated that long-term outcomes of preterm infants did not differ between the groups classified according to the BW at two years of age. This has leaded to the conclusion that severe IVH is alone represents a significant risk factor for poor neurodevelopmental outcome in this already high-risk population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 28 publications
1
23
0
4
Order By: Relevance
“…IVH, PVL, BPD, NEC, sepsis, and ROP have all been associated with neurodevelopmental impairment. [26][27][28][29][30] Other studies have shown higher rates of cerebral palsy, cognitive impairment, and behavioral problems among those born at very early gestations, 31-34 thus putting extremely preterm infants with major neonatal morbidities at high risk for significant impairment later in life.…”
Section: Tablementioning
confidence: 99%
See 1 more Smart Citation
“…IVH, PVL, BPD, NEC, sepsis, and ROP have all been associated with neurodevelopmental impairment. [26][27][28][29][30] Other studies have shown higher rates of cerebral palsy, cognitive impairment, and behavioral problems among those born at very early gestations, 31-34 thus putting extremely preterm infants with major neonatal morbidities at high risk for significant impairment later in life.…”
Section: Tablementioning
confidence: 99%
“…11 Although populationbased data are available for some countries, 1,4,5 comparable data in the United States are limited. 13,20 The primary aim of the present study was to assess the rates of mortality and major morbidity among extremely preterm infants (22)(23)(24)(25)(26)(27)(28) weeks' gestation) born in California, by using data collected from 2007 through 2011 by the California Office of Statewide Health Planning and Development (OSHPD). We also examined the rates of neonatal interventions and timing of death for each gestational week between 22 and 28 weeks.…”
mentioning
confidence: 99%
“…These patient characteristics and short-term clinical outcomes were chosen because of their established adverse effect on the primary outcome of this study, i.e. long-term neurodevelopmental outcome [18,19,20,21]. We did not correct for cystic periventricular leukomalacia (cPVL) since the incidence of this outcome was extremely low in both groups.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have shown the negative impact of severe IVH on mortality and neurodevelopmental outcome of affected patients [8,9], but there is no agreement about the impact of low-grade IVH. Although data from large population studies suggest that preterm infants with IVH grades I and II are not at risk for longterm neurodevelopmental impairment [10,11], other studies indicate that this population is vulnerable to poor outcome [12][13][14].…”
Section: Introductionmentioning
confidence: 99%